Über die Werte einer im Kreise holomorphen Funktion - Gomberg, A. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Гомберг. О значениях функций, голоморфных в круге A. Gombergas. Apie holomorfinės skritulyje funkcijos reikšmes